UJI AKTIVITAS ANTIBAKTERI DAUN JUKUT PENDUL (Kyllinga nemoralis) YANG DIPEROLEH DARI KOTABARU, KALIMANTAN SELATAN, INDONESIA - Soemarie, Yulistia Budianti; Niasti, Ignalia; Hasniah (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2024)
The use of antibiotics as acne treatment is often used as the main treatment by the community. Natural acne treatments that are easily available should be developed to replace chemical products, such as the jukut pendul plant (Kyllinga nemoralis). The purpose of this study was to determine the antibacterial activity of jukut pendul leaves against Propionibacterium acnes. The sample was determined, extracted by maceration method using 70% ethanol, then fractionated with water, ethyl acetate, and n-hexane solvents. Phytochemical screening on ethanol extract, n-hexane fraction, ethyl acetate fraction, and water fraction. Antibacterial activity tests were conducted on extracts and fractions of jukut pendul leaves with concentrations of 5%, 10%, and 15%. Antibacterial activity testing of 5% concentration ethanol extract produced inhibition of 9.5 mm (medium), 10% 9.6 mm (medium), 15% 10.16 mm (strong). The n-hexane fraction of 5%, 10% and 15% concentration was 6 mm (medium). Ethyl acetate fraction of 5% concentration was 9 mm (medium), 10% 9.6 mm (medium), 15% 11.2 mm (strong). Water fraction of 5% and 10% concentration was 6 mm (medium), 15% concentration was 8.3 mm (medium). Keywords: Antibacterial, Jukut Pendul (Kyllinga nemoralis), Propionibacterium acnes